Molecular characterization of Vibrio cholerae O1 and non-O1 from human and environmental sources in Malaysia - Son, Radu; Y.K, Ho; Samuel, Lihan; Yuherman, -; G., Rusul; R. M., Yasin; J., Khair; N., Elhadi (Cambridge University Press, 1999)
A total of 31 strains of Vibrio cholerae O1 (10 from outbreak cases and 7 from surface water) and non-O1 (4 from clinical and 10 from surface water sources) isolated between 1993 and 1997 were examined with respect to presence of cholera enterotoxin (CT) gene by PCR-based assays, resistance to antibiotics, plasmid pro®les and random ampli®ed polymorphic DNA (RAPD) analysis. All were resistant to 9 or more of the 17 antibiotics tested. Identical antibiotic resistance patterns of the isolates may indicate that they share a common mode of developing antibiotic resistance. Furthermore, the multiple antibiotic resistance indexing showed that all strains tested originated from high risk contamination. Plasmid pro®le analysis by agarose gel electrophoresis showed the presence of small plasmids in 12 (7 non-O1 and 5 O1 serotypes) with sizes ranging 1±3±4±6 MDa. The CT gene was detected in all clinical isolates but was present in only 14 (6 O1 serotype and 8 non-O1 serotype) isolates from environmental waters. The genetic relatedness of the clinical and environmental Vibrio cholerae O1 and non- O1 strains was investigated by RAPD ®ngerprinting with four primers. The four primers generated polymorphisms in all 31 strains of Vibrio cholerae tested, producing bands ranging from !250 to 4500 bp. The RAPD pro®les revealed a wide variability and no correlation with the source of isolation. This study provides evidence that Vibrio cholerae O1 and non-O1 have signi®cant public health implications.